A qualitative exploration of how communicative and direct experiences shape students' dietary climate awareness - Anna Steinfeldt; Tina Bartelmeß (Discover Sustainability)
Abstract This study explores the development of dietary climate awareness and its influence on dietary changes among university students. Given the substantial role of food systems in greenhouse gas emissions, fostering climate-conscious eating is critical. The study investigates communicative and experiential factors that shape students' awareness and transitions to vegan, vegetarian, or flexitarian diets. Episodic interviews were conducted with 18 students from the University of Bayreuth who made dietary changes within the past five years. Data were analysed using qualitative content analysis. Results show that dietary transitions are highly individualized and typically unfold over time, following a non-linear process consistent with the Transtheoretical Model. Climate awareness and behaviour change were shaped by institutional, media, and interpersonal communication, as well as direct experiences such as studying abroad or witnessing environmental degradation. Key influences included family norms, peer networks, media content (e.g., documentaries), and transitional life phases. Specific turning points—such as pivotal conversations or impactful media—often initiated dietary shifts. Participants who reached a stable dietary pattern frequently became advocates within their social environments, contributing to broader norm changes. The study highlights the communicative and experiential dynamics underlying climate-conscious eating among students and offers insights for strategies to promote sustainable dietary behaviour in this demographic.